A Qualitative Analysis of Pets as Suicide Protection for Older People. (3rd March 2020) - Young, Janette; Bowen-Salter, Holly; O'Dwyer, Lisel; Stevens, Kristen; Nottle, Carmel; Baker, Amy
ABSTRACT: An unanticipated finding during research on the role that pets play in the health of older adults was that pets had protected some from suicide. Given that older people are more vulnerable to fatal first attempts, understanding protective factors in this population is vital. Twelve older adults interviewed about the role of pets on their health spoke overtly of suicide ( n = 2), obliquely referred to suicidal ideation ( n = 5), or reported high levels of distress and/or depression ( n = 5). These participants were aged 60 to 83 years; five were male and seven were female. Interview transcripts were analyzed using a qualitative descriptive thematic approach in order to understand how they (collectively) identified pets as protecting them from suicide. Concepts of function, presence, known-ness, and reciprocity emerged as factors protective against suicide. These factors may counter those already identified as underpinning suicidal behavior: perceived burdensomeness and social alienation. For some older people, relationships with nonhuman others may be protective against suicide. Systemic responses that incorporate human–animal relationship awareness need to be explored to promote and protect some humans while also considering the impact on pets.